Elevated serum level of the vascular endothelial growth factor predicts radiographic spinal progression in patients with axial spondyloarthritis. Issue 12 (16th August 2013) - Poddubnyy, Denis; Conrad, Kristina; Haibel, Hildrun; Syrbe, Uta; Appel, Heiner; Braun, Jürgen; Rudwaleit, Martin; Sieper, Joachim
Abstract : Objective: To investigate the role of serum vascular endothelial growth factor (VEGF) as a predictor of radiographic spinal progression in patients with axial spondyloarthritis (axSpA). Methods: Altogether, 172 patients with definite axSpA (95 with ankylosing spondylitis and 77 with non-radiographic axSpA) were included in this study. Spinal radiographs obtained at baseline and after 2 years of follow-up were scored independently by two trained readers in a concealed and randomly selected order according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) scoring system and for the presence of syndesmophytes. Radiographic spinal progression after 2 years was defined as (1) mSASSS worsening by ≥2 units, and (2) new syndesmophyte formation or formation of a bridging syndesmophyte from two single syndesmophytes. Serum VEGF levels were detected at baseline. Results: Mean baseline VEGF values were significantly higher in patients with mSASSS worsening by ≥2 units after 2 years (n=22) than in those without progression (562±357 vs 402±309 pg/mL, respectively, p=0.027) and in patients with syndesmophyte formation (n=18) again as compared with those without new bone formation (579±386 vs 404±307 pg/mL, respectively, p=0.041). VEGF as a predictor of radiographic spinal progression performed especially well in patients who were already at high risk for such a progression due to the presence of syndesmophytes at baseline (n=48). In these patients, a VEGF serum level of >600 pg/mL had a sensitivity of 53%, a specificity of 97% and an OR=36.6 (95% CI 3.9 to 341.5) as a predictor of mSASSS worsening by ≥2 units. For syndesmophyte formation, elevated VEGF demonstrated a sensitivity of 47%, a specificity of 94% and an OR=13.6 (95% CI 2.4 to 78.3). Conclusions: An elevated serum level of VEGF (>600 pg/mL) is highly specific as a predictor of radiographic spinal progression in patients with axSpA, especially in patients who are at high risk for further progression due to the presence of syndesmophytes.